Intriguing differences in hydrogen adsorption in CPO-27 materials induced by metal substitution1. Issue 9 (7th March 2015) - Rosnes, Mali H.; Opitz, Martin; Frontzek, Matthias; Lohstroh, Wiebke; Embs, Jan Peter; Georgiev, Peter A.; Dietzel, Pascal D. C.
<x xml:space="preserve">Abstract</x> We present a comparative study of hydrogen gas adsorption experiments on CPO-27–Cu and –Mn. The initial isosteric heat of adsorption in CPO-27–Cu is low for a material containing open metal sites and in contrast to the other members of the CPO-27 series, including the Mn compound.